Accelerated human cardiac diffusion tensor imaging using simultaneous multislice imaging. Issue 3 (21st March 2014) - Lau, Angus Z.; Tunnicliffe, Elizabeth M.; Frost, Robert; Koopmans, Peter J.; Tyler, Damian J.; Robson, Matthew D.
<x xml:space="preserve">Abstract</x> Purpose To demonstrate the feasibility of accelerating measurements of cardiac fiber structure using simultaneous multislice (SMS) imaging. Methods SMS excitation with a blipped controlled aliasing (CAIPI) readout was incorporated into a diffusion‐encoded stimulated echo pulse sequence to obtain diffusion measurements in three separate slices of the heart (8‐mm thickness, 12‐mm gap). A novel image entropy‐based method for removing image ghosts in blipped CAIPI acquisitions is also introduced that enables SMS imaging of closely spaced slices in the heart. Results The average retained signal‐to‐noise ratio (SNR) using this acquisition scheme is 70% ± 5%, higher than the standard <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3xd4cv37" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1/3</alternatives> = 57% SNR penalty with three‐fold acceleration. No significant difference was observed in the apparent diffusion coefficient and helix angle diffusion parameters between a time‐equivalent conventional single‐slice scan and the three‐fold accelerated SMS acquisition. A 10% mean bias was observed in fractional anisotropy between single‐slice and SMS acquisitions. Conclusion The new sequence was used to obtain high‐quality diffusion measurements in three closely spaced cardiac slices in a clinically feasible nine breath‐hold examination. The accelerated multiband sequence is anticipated to improve quantitative measurements of cardiac microstructure by reducing the number of breath‐holds required for the scan, making it practical to incorporate diffusion tensor measurements within a comprehensive clinical examination. Magn Reson Med 73:995–1004, 2015. © 2014 Wiley Periodicals, Inc.